Impact of Financial Literacy, Investment Training, and Risk Attitudes on Investment Decisions: The Moderating Role of Self-Efficacy in Public University Students in Surabaya - Bhakti, Ilham Dio; Haryati, Tantina (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to examine how financial literacy, investment training, and risk attitudes influence investment decisions among students of public universities in Surabaya, with self-efficacy as a moderating variable. Methodology: A quantitative approach was employed, with data collected from 100 students using a structured questionnaire. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results: Financial literacy, investment training, and risk attitudes have a significant influence on investment decisions. Self-efficacy strengthens the influence of financial literacy and investment training on investment decisions but does not moderate the relationship between risk attitudes and investment decisions. Findings: The study highlights the role of self-efficacy as an important psychological factor that enhances financial decision-making among students. Novelty: This research introduces self-efficacy as a moderating variable, a relatively rare approach in studies exploring the relationship between financial literacy and investment decisions, especially among Indonesian students. Originality: The study presents a unique model that integrates cognitive, experiential, and psychological variables, emphasizing the significance of self-efficacy in financial behavior. Conclusion: The findings suggest that financial education programs should focus on enhancing self-efficacy to improve investment decision-making. Type of Paper: Empirical Research